A New Perspective on the Development of the Great Arctic Cyclone in August 2012. Issue 17 (29th August 2022) - Chen, L. J.; Fu, G.; Li, P. Y.
Abstract: The evolutionary process of "The Great Arctic Cyclone (AC) of August 2012" (hereafter named as AC2) was investigated by using the Arctic System Reanalysis version 2 data, from a new perspective of two cyclones' merging. The evolution of AC2 was affected by the merging process with a pre‐existing AC (hereafter named as AC1) at lower‐levels, and the impact of the two tropopause polar vortices (TPVs). The AC2's development showed a slowdown at the early stage of merging (before 00 UTC 5), and a rapid intensification at the later stage (after 00 UTC 5). The diagnostic results based on Zwack‐Okossi equation showed that, at the early stage of merging when two TPVs had not merged, despite AC2's intensification was favored by vorticity advection provided by the upper‐level jet stream, the warm advection supporting AC2's development, which was prevented by TPV2. AC2 weakened due to the joint influences of cold advection induced by the cold core beneath the TPV2 and AC1's cyclonic circulation at lower‐levels. At the later stage of merging, AC2 rapidly intensified due to the joint influences of warm advection produced by the warm air advected from warm core above the merged TPV by the upper‐level jet stream, and the warm advection induced by enhanced lower‐level baroclinicity near the warm front. Diabatic heating near the upper‐ and lower‐level fronts also played an important role in promoting AC2's development through its whole time. Plain Language Summary: Arctic cyclones (ACs) have gained much attention recently on account of the considerable contribution to the rapid loss of summer Arctic sea ice. A severe AC, which made a historical new record of minimum Arctic sea ice extent in August 2012, was studied by using Arctic System Reanalysis version 2 data. The developing mechanism of this AC was investigated based on diagnostic analyses. The results showed that the earlier weakening and later intensification of this AC was jointly affected by the forcing of the upper‐level tropopause polar vortices and its merging with a lower‐level pre‐existing AC. Key Points: The evolution of an extreme Arctic cyclone (AC) in August 2012 was re‐analyzed by using Arctic System Reanalysis version 2 data The development of the AC was diagnosed from a new perspective of two cyclones' merging under the impact of two tropopause polar vortices Schematic diagrams were illustrated to explain the earlier weakening and subsequent rapid intensification of this AC